1996
DOI: 10.1144/gsl.qjegh.1996.029.p3.08
|View full text |Cite
|
Sign up to set email alerts
|

Observations on soil permeability, moulding moisture content and dry density relationships

Abstract: Increasing use of the coefficient of permeability as a quality control parameter for earthworks, in particular for landfilling, has resulted in many engineers looking to predict coefficients of permeability for clays from more widely available but often widely scattered data. In a number of cases this has led erroneously to the interpretation of the moisture contentcoefficient of permeability relationship as the direct inverse of the moisture content-density relationship. This paper reexamines the original the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Laboratory tests, that were carried out have shown that further enhancement of the content of fine fractions, when the maximum soil compaction have been reached, contribute to the increase of the amount of water in the soil sample, that is necessary to obtain the optimal moisture content (OMC), while the dry density decreases (MDD) -see Figures 5 and 6. Non-linear dependence between the compactibility parameters (the maximum dry density and optimum moisture content), that were obtained in the Proctor Compaction and the fine fraction content was also confirmed by many papers regarding both natural and stabilized soils (Hossain et al, 2016;Sulewska & Tymosiak, 2018;Gupta & Thomas, 2013;Wright et al, 1996;Zhemchuzhnikov et al, 2016;Osouli, Salam, Tutumluer, & Shoup, 2017). This clear relationship developed between the compactibility parameters and the CBR value causes that numerous scientific studies attempt to predict the CBR value based on Maximum Dry Density (MDD), Optimum Moisture Content (OMC), the content of sand, clay or silt fractions (Sreelekshmypillai & Vinod, 2017;Katte, Mfoyet, Manefouet, Wouatong, & Bezeng, 2019).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Laboratory tests, that were carried out have shown that further enhancement of the content of fine fractions, when the maximum soil compaction have been reached, contribute to the increase of the amount of water in the soil sample, that is necessary to obtain the optimal moisture content (OMC), while the dry density decreases (MDD) -see Figures 5 and 6. Non-linear dependence between the compactibility parameters (the maximum dry density and optimum moisture content), that were obtained in the Proctor Compaction and the fine fraction content was also confirmed by many papers regarding both natural and stabilized soils (Hossain et al, 2016;Sulewska & Tymosiak, 2018;Gupta & Thomas, 2013;Wright et al, 1996;Zhemchuzhnikov et al, 2016;Osouli, Salam, Tutumluer, & Shoup, 2017). This clear relationship developed between the compactibility parameters and the CBR value causes that numerous scientific studies attempt to predict the CBR value based on Maximum Dry Density (MDD), Optimum Moisture Content (OMC), the content of sand, clay or silt fractions (Sreelekshmypillai & Vinod, 2017;Katte, Mfoyet, Manefouet, Wouatong, & Bezeng, 2019).…”
Section: Resultssupporting
confidence: 54%
“…The results are presented in Table 1. Conducted research, as well as analysis performed by other authors, point to some regularities in changes of the compactibility parameters of tested soil samples (Sulewska & Tymosiak, 2018;Gupta & Thomas, 2013;Wright, Walden, Sangha, & Langdon, 1996;Zhemchuzhnikov, Ghavami, & Casagrande, 2016;Roy, 2013). Mentioned changes depending on the content of fines and sands in testes soil are clearly visible (Satyaveni, Sridevi, Sivanarayana, & Prasad, 2018).…”
Section: Resultsmentioning
confidence: 67%
“…Clod theory predicts (e.g. Wright et al, 1996;Trenter, 1999;Osinubi and Eberemu, 2006) that the fluid flow through the clay will remould and aggregate the clay clod particles (through partial fluidization and flocculation) and that the dominant flow during recharge will be inter-clod. Experimental evaluation of clod theory has established (e.g.…”
Section: Ground-water Mound Modellingmentioning
confidence: 99%
“…Exactly how the microstructure changes will depend on the conditions of placement, e.g. compactive effort, moisture content and the size of clods being compacted to form the liner (Wright et al 1996).…”
Section: Deformation and Fluid Flow In Mudrocksmentioning
confidence: 99%